Penerapan Pembelajaran Jurnalistik Olahraga pada Mahasiswa Pendidikan Jasmani FKIP Universitas Megarezky melalui Kunjungan ke Redaksi Harian Fajar - Aminuddin Aminuddin (PT. Mediatama Zayna Indonesia, 2024)
The world of journalism today is no longer a hobby but has transformed into a profession that has begun to be looked at. Sports journalism is one of the courses in the curriculum of the physical education program at FKIP Megarezky University. The main focus of sports journalism learning is learning outcomes so that students have skills in the field of journalism which is growing rapidly in Indonesia and are not focused only on becoming a PE teacher. 40 students accompanied by 2 lecturers visited the Fajar Daily editorial office to learn and apply the knowledge they got on campus. The outputs obtained from this activity are (1) strengthening cooperative relations with the world of industry (Fajar Daily) in supporting cooperation in learning sports journalism. (2) direct experience for students in the world of journalism. (3) Curriculum cooperation.